2019
DOI: 10.1002/cphc.201900024
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Thermodynamics Unveils How Ions Influence an Aqueous Diels‐Alder Reaction

Abstract: The kinetics of Diels‐Alder (DA) reactions in water has been known to be altered by salts for a long time. Yet the question how salts influence the reaction rate, either as rate‐enhancing or rate‐reducing additives, has so far remained unresolved. Conflicting hypotheses involve (i) indirect salt contributions through the modulation of internal pressure and (ii) making (or breaking) of the so‐called “water‐structure” by salts that strengthen (or weaken) the hydrophobic effect. In contrast to the qualitative nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(200 reference statements)
0
4
0
Order By: Relevance
“…They also concluded that ammonium salts bearing long alkyl groups promote the dissolution of the nonpolar reactants by rearranging water molecules up to a second solvation shell around the dissolved salts, thus behaving as anti-hydrophobic or salting-in agents. In another study, Shimizu and coworkers investigated the effect of several rate-enhancing salts (e.g., LiCl, guanidinium sulfate) and rate-reducing salts (e.g., NaClO 4 , guanidinium acetate) for the same reaction, demonstrating that the interactions between ions and diene 54 are crucial for controlling the reaction rate [94]. A rate reduction was observed for the reaction in the presence of rate-reducing salts, which show a preferential interaction with diene, and is consistent with the increased 54 solubility.…”
Section: The Water Effect: Experimental and Theoretical Studiesmentioning
confidence: 99%
“…They also concluded that ammonium salts bearing long alkyl groups promote the dissolution of the nonpolar reactants by rearranging water molecules up to a second solvation shell around the dissolved salts, thus behaving as anti-hydrophobic or salting-in agents. In another study, Shimizu and coworkers investigated the effect of several rate-enhancing salts (e.g., LiCl, guanidinium sulfate) and rate-reducing salts (e.g., NaClO 4 , guanidinium acetate) for the same reaction, demonstrating that the interactions between ions and diene 54 are crucial for controlling the reaction rate [94]. A rate reduction was observed for the reaction in the presence of rate-reducing salts, which show a preferential interaction with diene, and is consistent with the increased 54 solubility.…”
Section: The Water Effect: Experimental and Theoretical Studiesmentioning
confidence: 99%
“…Note that the same 𝑉 𝐸 was used in Eq. ( 2) for calculating 𝐺 𝑢1 ′ and 𝐺 𝑢2 ′ [59,61]. By doing so, the solvation shell relationships, Eqs.…”
Section: Solvation Shell Contribution To the Kirkwood-buff Integralsmentioning
confidence: 99%
“…for example, a cosolvent larger in molecular size than water has a negative contribution to 𝐺 𝑢2 ′ from the excluded volume effect [59,61].…”
Section: Solvation Shell Contribution To the Kirkwood-buff Integralsmentioning
confidence: 99%
“…However, kinetics and thermodynamics of aggregation, as stated in Section 2.3, are different [8,13,18,19]. Different phenomena require different theoretical approaches, and yield different results [8,13,18,19].…”
Section: Point D: From Kbis To Microscopic Understandingmentioning
confidence: 99%